FORESTS AND NATIONAL SECURITY - Arce Rojas, Rodrigo (2021)
The article deals with the relationship between forests and national security with the aim of contributing to raising the awareness of the authorities linked to National Security and Defense in order to increase their commitment and quality of participation in the objectives of conservation and sustainable use of forest biodiversity. From the reflection it is concluded that national security is the situation in which the State has guaranteed its independence, sovereignty and integrity, and the population the fundamental rights established in the Constitution. It is therefore a complex and multidimensional concept that goes beyond the reduced vision of threats to territorial integrity and addresses various considerations, including environmental dimensions. Forests are related to national security from the perspective of human security (food, water, health, energy, climate and economic) and management (territorial, environmental, disaster risk reduction and socio-environmental conflicts). Despite significant progress in terms of conservation and sustainable use of forests, there are still major problems such as the loss of forests as a result of direct and structural factors, which constitutes a threat to national security. Beyond technical, legal or market solutions, it is important to explore other options such as biodevelopment proposals that place respect for all living manifestations (human and non-human) as the axis of human thinking, feeling and acting, that is, to incorporate biopluralist perspectives that overcome the anthropocentric paradigm that has dominated.